PENGGUNAAN MODUL E LEARNING SISTEM REPRODUKSI MANUSIA UNTUK MENINGKATKAN MINAT SISWA DALAM MENGOPTIMALKAN POTENSI KECERDASAN MAJEMUK - Dewi Andayani (Biotik, 2017)
The study titled is using human reproduction system E-learning module to improve student's interest in optimizing the potential of multiple intelligence to increasing student interest in optimizing the potential of multiple intelligences in studying human reproductive system concept by using E learning module. This research was conducted on March 10 until March 25, 2015. The method used is experimental and descriptive with a sample size of 60 students consisting of 30 students class XI-IPA 2 and 30 students class XI-IPA 3. Data analysis used to know the difference of improvement of cognitive learning result is t test at significant level 0,05. Result of t test of student interest increase obtained t scor 16,3 â‰¥ t table (1,98). The conclusion of this research is the use of human reproduction system module through e learning can increase student interest in maximizing the potential of multiple intelligences.